2012
DOI: 10.1097/hjh.0b013e3283588d73
|View full text |Cite
|
Sign up to set email alerts
|

The effect of coffee consumption on blood pressure and the development of hypertension

Abstract: Low-quality evidence did not show any statistically significant effect of coffee consumption on BP or the risk of hypertension. Given the quality of the currently available evidence, no recommendation can be made for or against coffee consumption as it relates to BP and hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0
8

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(84 citation statements)
references
References 33 publications
(91 reference statements)
5
68
0
8
Order By: Relevance
“…A recent meta-analysis of 10 randomized controlled trials and 5 cohort studies assessed BP and the incidence of arterial hypertension in coffee consumers did not find significant changes in mean systolic or diastolic BP in coffee drinkers compared with the control group. Evidence analyzed from this large study showed no clinically important effects of long-term coffee consumption on BP or risk of arterial hypertension [7,[15][16][17]. Considering the effects of caffeine, controlled interventional studies show that in normal adults, even high-dose caffeine does not affect prevailing cardiac rhythm and rate.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…A recent meta-analysis of 10 randomized controlled trials and 5 cohort studies assessed BP and the incidence of arterial hypertension in coffee consumers did not find significant changes in mean systolic or diastolic BP in coffee drinkers compared with the control group. Evidence analyzed from this large study showed no clinically important effects of long-term coffee consumption on BP or risk of arterial hypertension [7,[15][16][17]. Considering the effects of caffeine, controlled interventional studies show that in normal adults, even high-dose caffeine does not affect prevailing cardiac rhythm and rate.…”
Section: Discussionmentioning
confidence: 76%
“…The acute effects of coffee are transient, and, with regular intake, tolerance develops to its hemodynamic and humoral effects [14,15]. A recent meta-analysis of 10 randomized controlled trials and 5 cohort studies assessed BP and the incidence of arterial hypertension in coffee consumers did not find significant changes in mean systolic or diastolic BP in coffee drinkers compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The cardiovascular effects of coffee drinking depend in part on coffee preparation method and individual characteristics (eg, hypertension and hyperlipidemia). [1][2][3] There are 2 main methods of coffee preparation: filtered and unfiltered. Filtered coffee, also known as drip-brewed coffee, is the most common mode of preparation in the United States and involves brewing the coffee through a paper filter.…”
Section: Coffeementioning
confidence: 99%
“…У больных с повышенным АГ применение диетических подхо-дов к коррекции гипертонии (исследование DASH) в комбинации с физической нагрузкой сопрово-ждалось более выраженным снижением АД и уменьшением ГЛЖ, чем только диета DASH [360]. Что касается употребления кофе, то недав-ний систематический обзор показал, что качество большинства проведенных исследований (10 РКИ и 5 когортных) недостаточно высоко, чтобы на их основании можно было разрешать или запрещать кофе применительно к АГ [361].…”
Section: другие изменения питанияunclassified